Chiral Phosphoric Acid: A Powerful Organocatalyst for the Asymmetric Synthesis of Heterocycles with Chiral Atropisomerism - Shao, You‐Dong; Cheng, Dao‐Juan (ChemCatChem, 2021)
The past two decades have witnessed unprecedented development and advancement of chiral phosphoric acid catalysis. Therefore, it is not surprising that the attempts to synthesize enantioenriched axially chiral compounds via chiral phosphoric acid catalysis have achieved fruitful results in recent years although this area of research is still in its infancy. A number of structurally important heterocycles with chiral atropisomerism have been successfully designed and prepared by chiral phosphoric acid promoted transformations involving diverse strategies: including direct coupling, de novo formation of a heterocyclic ring and functionalization of prochiral or racemic substrates. In this minireview, we would like to highlight the advances in the field of atropisomeric heterocycles construction enabled by chiral phosphoric acid catalysis. In addition, this Minireview is organized based on the different types of atropisomeric heterocyclic frameworks generated covering quinoline, pyrrole, indole, benzimidazole, quinazolinone, isoindolinone, urazole, pyrazole and so on. We hope that this Minireview will motivate continuous interest on chiral phosphoric acid catalyzed atroposelective reactions. Organocatalysis: The advances in the field of chiral phosphoric acid catalyzed reactions for the asymmetric synthesis of heterocycles with chiral atropisomerism, including quinoline, pyrrole, indole, benzimidazole, quinazolinone, isoindolinone, urazole and pyrazole were reviewed. The substrates scope, mechanisms, limitations and applications were discussed.